Human trafficking and regulating prostitution - Samuel Lee; Petra Persson (Research Institute of Industrial Economics (IFN), 2013)
We study human trafficking in a marriage market model of prostitution. When trafficking is based on coercion, trafficking victims constitute a non-zero share of supply in any unregulated prostitution market. We ask if regulation can eradicate trafficking and restore the outcome that would arise in an unregulated market without traffickers. All existing approaches - criminalization of prostitutes (the traditional model), licensed prostitution (the Dutch model), and criminalization of johns (the Swedish model) - fail to accomplish this goal, but we show that there exists an alternative regulatory model that does. Political support for regulation hinges on the level of gender income inequality.
Keywords: D10; J16; J47; J49; K14; K23; 330; Prostitution; Trafficking; Contemporary slavery; Marriage; Illegal goods